Patient decision aid in vaccination: a systematic review of the literature. (2nd April 2020) - Bruel, S.; Leclercq, T.; Ginzarly, M.; Botelho-Nevers, E.; Frappé, P.; Gagneux-Brunon, A.
ABSTRACT: Introduction: Decision-making for patients and their families in the field of vaccination is difficult, involving many multidimensional factors. The complexity of this process is directly responsible for the phenomenon of vaccine hesitancy. Decision aids are instruments that provide information on a specific subject, explaining the advantages and disadvantages of a decision in a personalized way, thus clarifying the patient's values. Areas covered: A systematic review using PRISMA guidelines was conducted to carry out an inventory of decision aids in the field of vaccination and assess their impact on vaccine coverage and decisional conflict. Expert opinion: Decision aids reduce decision-making conflict and could be good tools to address the phenomenon of vaccine hesitancy. It seems essential to integrate health professionals and patients into the design of future decision aids. This would simplify the use of these tools during the consultation. However, their effect on vaccine coverage remains uncertain. Further studies seem necessary in order to conclude that vaccination coverage is effective.